بلاغة الخطاب القرآني وأثرها في المتلقي - توامة, عاشور (قــــــراءات, 2019)
تهتم هذه الدراسة ببلاغة الخطاب القرآني وتأثيرها في المتلقي، وتوجيهه في أفق المقاربة النقدية البلاغية العربية، وصلتها بالتصورات والأطر المعرفية لنظرية التلقي من خلال بعض التجليات البيانية في رحاب القرآن الكريم وآليات فاعلية تأثيراتها في المتلقي، الذي يتموقع بين حرية الإطلاق الفكري وقيد التحديد اللغوي، وذلك بالتركيز على خطاب الاعتبار في القرآن الكريم، ومدى توجهه نحو المتلقي لما يتوافر على سمة من سمات الإعجاز البياني، ولما يتضمنه من أبعاد نفسية وجمالية، تحمل المتلقي على الإنصات لقوة المحاجة العقلية ووضوح البينة. ومما لا شك فيه، أن للقرآن الكريم أثرا واضحا في تطور البلاغة العربية، وفي صقل الذوق الفني الرفيع، وفي تشييد بنية الخطابات وتحليلها، وفي دعوة المتلقي إلى هذا التأمل البلاغي لاستشعاره والانفعال به في إحداث الاستجابة الجمالية والتفسيرية، كما يمكن التطرق إلى الجهد النقدي البلاغي في فهم واستيعاب الظاهرة الأدبية عبر عمليتي الإنتاج والتلقي. Abstract This study is concerned in eloquently discourse of the Quran and its impact on the recipient, and guide him to understand the Quran according to the standards of Arabic rhetorical eloquence, and its relate to the perceptions and cognitive frames to the theory of receiving, through the influence of metaphor and simile and metaphor tools etc, in the Quran and the mechanics of the effectiveness of their effects in the recipient which Positioning between the liberty in absolutely intellectual, and specifically linguistic from the Quran, by focusing on the speech of prestige in the Quran, and its orientation towards the receiver that has a sign of Miracles chart signs, and it Includes psychological and aesthetic dimensions, bearing on the receiver to listen to the mental strength of the argument and clarity of the evidence. It is no doubt that the Holy Quran has a clear impact in the evolution of Arabie Rhetoric, by training the receiver on the artistic taste and high speech, elevate the structure of the speeches and analysis them and by calling the receiver to the rhetorical assimilation to sense and influence him to occur aesthetic and interpretive Response. The effort to monetary and rhetorical can also be addressed in understanding the literary phenomenon.